Penerapan Teknik Batuk Efektif untuk Mengatasi Bersihan Jalan Nafas Tidak Efektif pada Pasien Tuberkulosis Paru (Studi Kasus): Implementation of Effective Cough Technique to Overcome Ineffective Airway Clearance in Pulmonary Tuberculosis Patients (Case Study) - Mawar, Selvia; Minardo, Joyo (Universitas Ngudi Waluyo, 2025)
Coughing accompanied by secretions is a common complaint experienced by tuberculosis patients. The accumulation of thick and difficult-to-expel secretions results in ineffective airway clearance. Effective coughing with the correct technique is expected to address that issue. The purpose of the research is to provide an overview of the application of effective coughing techniques to address airway clearance issues in tuberculosis patients to expel sputum. The research method is a descriptive case study using nursing process management over 3 days. The research results show that during the assessment, patients reported having a productive cough that has been difficult to expel for 3 months, RR: 26 breaths per minute, SPO2: 96%. The nursing diagnosis established was ineffective airway clearance, with implementation involving effective coughing. Upon evaluation, the patient reported that the coughing had decreased compared to the previous day, felt more refreshed, and did not appear lethargic. The respiratory rate was 20 breaths per minute, and the oxygen saturation was 98%. The outcome of the management is that the problem has been resolved. There is a need for health promotion about the benefits of effective coughing for tuberculosis patients.